(untitled) (The Research of Medical Science Review, 2025)
This study is to investigate fetal hemodynamics in pregnant women suffering from severe anemia, a condition prevalent in Pakistan where a hypoxic environment is common. Severe maternal anemia during pregnancy poses significant risks to both the mother and the fetus. Using advanced diagnostic techniques such as Doppler ultrasound, we will measure various parameters of fetal blood flow and vascular resistance. This will provide a detailed understanding of how the fetus compensates for the lack of oxygen. The objective of the study is to evaluate the placental anemia using umbilical artery and middle cerebral artery index through the cerebral placental ratio. Maternal anemia is a hypoxic condition that could be responsible for the redistribution of fetal blood flow. This study includes 155 pregnant women from Kishwar Sultana Hospital. Ultrasound was performed on all patients. Statistical analysis was performed using SPSS v 25.0 Out of 155 patients,38 women (24.5%) age is 19 to 23 years, 55 women (35.5%) age is 24 to 28 years, 58 women (37.4%) age is 29 to 33 years, and 4 women (2.6%) age is more than 34 years. Out of 155 pregnant women,29 women (18.7%) with history of hypertention,37 women (23.9%) with history of diabetes, 32 women (20.6%) with history of hypertension and diabetes and 57 women (36.8%) with no history. Out of 155 pregnant women,17 women (11%) with gestational age 21-25, 61 women (39.4%) with gestational age 26-30, 66 women (42.6%) with gestational age 31-35 and 11 women (7.1%) with gestational age more than 36. Out of 155 pregnant women, 91 women (58.7%) with parity 0-1 and 64 women (41.3%) with parity 2-3. Cerebroplacental ratio is highly sensitive in diagnosing hemodynamically compromised fetuses and very useful for the prediction of adverse perinatal outcome in these fetuses.